Bodei, Remo (2014). Imaginar otras vidas: Realidades, proyectos y deseos - Jordi Gil Garcia (Enrahonar: Quaderns de Filosofia, 2016)
Bodei, Remo (2014) Imaginar otras vidas: Realidades, proyectos y deseos Barcelona: Herder, 358 p. ISBN 978-84-254-3378-8